Analysis of Pancasila Learner Profile Sub-element of Self-Regulation of Phase B Elementary School Students - Julia Ayu Puspita; Aditya Dyah Puspitasari; Priyono Tri Febriyanto; Fatimah Azzahra’ (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
Self-regulation is an element that is part of the independent dimension which is part of the 6 pillars of Pancasila students. The research conducted has the aim of knowing the level of self-regulation in students, especially at elementary school age. In this study using descriptive quantitative methods. The subjects studied were elementary school students, especially phase B and elementary school teachers. In grade 3 and 4 elementary school students, there were 46 respondents. The technique used for data collection is a questionnaire. The results of this study are that elementary school students show that in self-regulation, the emotion regulation indicator gets 66.6%, the indicator of setting learning, achievement, and self-development goals and strategic plans to achieve them gets a percentage value of 82.6%, the indicator shows initiative and works independently gets a percentage value of 62.9%, the indicator develops self-control and self-discipline gets a percentage of 63.1%, the indicator is confident, resilient, and adaptive gets a percentage of 62.9%.